Pentingnya Penggunaan Merek Untuk Produk Makanan Ringan (Keripik) Bagi Masyarakat - Teng Berlianty; Agustina Balik; Triska Demmatacco (Universitas Negeri Semarang, 2022)
The use of brands on the packaging of snack products (chips) to mark the product, as a means of promotion, to show the quality of the product and the origin of the product. Legal counseling on trademarks was delivered by a lecturer in the civil section of the Unpatti Faculty of Law to the Wotay Village community as an effort to provide education on the importance of using brands. In addition, using a mark provides guarantees of legal protection for business actors/mark owners through online trademark registration at the Ministry of Law and Human Rights, Directorate General of Intellectual Property Rights.